Music Creation Durmanggala | Tabuh Kreasi Durmanggala - Putu Danendra Adi Bagaskara; Saptono Saptono; I Ketut Partha (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
The musical composition of Tabuh Kreasi Durmanggala is a karawitan composition that uses Semarandana gamelan as a medium of expression. This Durmanggala Creation Tabuh is a tabuh inspired by natural phenomenon hints implied in Lontar Roga Sanghara Bhumi, namely Durmanggala, which occurred in Kelan Traditional Village. The concept of this work uses the tri angga structure, which is still based on traditional principles. The tradition is well developed in terms of gending structure and techniques with the arrangement of musical elements such as tone, melody, rhythm, tempo, harmony, and dynamics. This masterpiece of Durmanggala creation was created because it contained four aspects that became the orientation of discussion in understanding ways to design new works, including aspects of ideas, aspects of concepts, and implementation of ideas and concepts into gamelan as a medium of expression, and consideration of taste.